The Hydrochemistry of Groundwater in Jambakan, Klaten Regency, Central Java Province, Indonesia - Ekha Yogafanny; Ardian Novianto; Rika Ernawati; Wibiana Wulan Nandari (Journal of Geoscience, Engineering, Environment, and Technology, 2019)
Jambakan is a hamlet in Bayat District, Central Java Province, Indonesia, which commonly has brackish groundwater. Its unique geological profile leads to variation in groundwater quality that is even found between adjacent wells. This study was designed to identify the quality and hydrochemical type of groundwater and the distribution of brackish groundwater in Jambakan. It employed a quantitative method to analyzethe data collected in the field survey and groundwater quality data (major ions). Meanwhile, the hydrochemical facies of groundwater was interpreted from the plots of major ions on trilinear and quadrilateral Piper diagrams. The results showed that some of the groundwater quality parameters in six wells, namely A6, A34, A38, A65, A67, and A73, had exceeded the standard thresholds. The parameters in question were TDS, EC, salinity, sodium, calcium, chloride, sulfate, magnesium, and hardness. Compared with the six wells, A40 and A45 had better quality. The distribution of brackish groundwater could not be modeled horizontally because salinity highly depends on rock layers where the observed wells are located. Based on the trilinear Piper plots, the groundwater consisted of four hydrochemical facies, namely magnesium bicarbonate, a mixed type, calcium chloride, and sodium chloride. Meanwhile, the quadrilateral Piper diagrams showed the presence of Type I (bicarbonate water), Type II (semi-bicarbonate water), Type III (evaporite water), and Type IVb-IVc (sulfate water) in the groundwater of Jambakan Hamlet.